Manfaat Kecerdasan Buatan pada Proses Belajar Mengajar di Pendidikan Tinggi - Zen Munawar; Sri Sutjiningtyas; Novianti Indah Putri; Rita Komalasari; Herru Soerjono (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research aims to determine the benefits of using artificial intelligence in the teaching and learning process in higher education. The contribution of computer science, especially artificial intelligence, to the field of education is very much felt. From robotic teaching to the emergence of automated systems for answer sheet analysis, artificial intelligence always helps lecturers and students. This study also investigates the educational implications of emerging technologies on how students learn and how the teaching and learning process in higher education is developing. Data analysis is carried out comprehensively on various analytical developments applied worldwide such as computer science techniques applied to the education sector so as to summarize and highlight the role of artificial intelligence in the teaching and learning process. The latest technological advances and the increasing speed of application of new technologies in higher education are explored to predict the nature of higher education today and in a world where artificial intelligence becomes part of the higher education structure. The results of the study indicate several challenges for higher education institutions and student learning in adopting this technology for the teaching and learning process, support from students, and administration and the need to explore further research directions.